2018
DOI: 10.12693/aphyspola.133.829
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Oxide Composites: Toward New Optical Materials

Abstract: Brief summary concerning properties of the polymer matrix incorporated with inorganic, e.g. oxide particles, micro/nanocomposites and opportunity to use these composites as optical materials for modern optics and optoelectronic devices is presented in the work. Structure and morphology of the several sets of the new polymer micro/nanocomposites based on the microcrystalline cellulose incorporated with micro/nanoparticle of various oxides (NaNO2, La1−xSmxVO4, La1−xEuxVO4 and K2Eu(PO4)(MoO4)), were prepared by "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…ln(k p − k)/S a = lnk s + (ρ − 1)lnC (3) The specific rates of decomposition of peroxides showed that with the increasing of peroxide concentration the numerical values of k p decrease. The increase in the concentration of peroxide leads to the decrease in the numerical values of k p .…”
Section: Colloids Interfaces 2019 3 X For Peer Review 3 Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…ln(k p − k)/S a = lnk s + (ρ − 1)lnC (3) The specific rates of decomposition of peroxides showed that with the increasing of peroxide concentration the numerical values of k p decrease. The increase in the concentration of peroxide leads to the decrease in the numerical values of k p .…”
Section: Colloids Interfaces 2019 3 X For Peer Review 3 Ofmentioning
confidence: 99%
“…where S a is the area of surface of the dispersed phase in 1 liter of mixture, C-is the initial concentration of peroxide in the system, ρ is the kinetic order of the reaction of the heterogeneous catalytic decomposition, k s is the rate constant of the decomposition of peroxide on the surface of the adsorbent. The Equation 2becomes an Equation (3). This determines the parameters of the heterogeneouscatalytic decomposition:…”
Section: Colloids Interfaces 2019 3 X For Peer Review 3 Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The filler performs many functions in the composite, providing the material with specific properties [1] [2]. The hybrid organic-mineral composites are produced with the incorporation of inorganic fillers in the structure of polymer [3] [4] [5]. The polymer matrix incorporated with inorganic particles forms the micro/nanocomposites that can be used in different fields of industry [1] [4].…”
Section: Introductionmentioning
confidence: 99%